The Role of Social Media Marketing in the Formation of Brand Loyalty with Brand Trust and Brand Engagement as Mediating Variables (Case Study of NPure Skincare Products) - Hartono , Soraya Farahdilla Dwi; Pakarti, Piji; Chasanah, Amalia Nur; Putra , Febrianur Ibnu Fitroh Sukono (Indonesia Banking School, 2025)
This study aims to determine the role of social media marketing in building brand loyalty for Npure skincare products, with a focus on brand trust and brand engagement as mediating variables. The method used in this research is to collect data obtained from distributing questionnaires totaling 115 respondents with the criteria of active social media users, have seen Npure skincare advertisements on Instagram social media and have made purchases at least 2 times and use Npure skincare. In analyzing data using SEM analysis assisted by smartPLS. From the results of the hypothesis testing that the researchers have done, the researchers found a positive influence between the two variables (social media marketing, brand engagement on brand loyalty) and the absence of the influence of brand trust on brand loyalty. The managerial implications of this study include the importance of developing interesting and interactive digital marketing strategies.